O ensino superior e a pessoa com deficiência: um olhar complexo sobre a UFAM - Ferreira, Rafael Lima Medeiros (2024)
The present work aims to analyze the inclusion of undergraduate students with disabilities at the Federal University of Amazonas (UFAM). To this end, a theoretical framework was constructed that supported the necessary discussions about the proposed theme. The aforementioned bibliographical survey took place through articles, dissertations and theses, available in libraries and databases, which discussed the topic of inclusion in higher education. Regarding methods, this study is characterized as qualitative research, cross-sectional, and can also be characterized as applied research and a case study of an exploratory and descriptive nature. The research subjects were undergraduate students, with or without disabilities, undergraduate professors and 3 sectors of UFAM, which work directly with students with disabilities. For data collection, 4 instruments were constructed and applied, virtually, from June to September 2023. The collected data was analyzed through content analysis and brought significant results about the universe investigated. Among the strengths and weaknesses, we can identify several actions that are carried out in favor of students with disabilities, in the same way that this group of individuals needs to deal with the most varied barriers that are imposed on them every day. In this way, the present study fulfilled its objective and raises serious discussions about the processes of inclusion and exclusion that are part of the university routine of students with disabilities at UFAM.